Proceedings of the 13th International Conference on Information Integration and Web-Based Applications and Services 2011
DOI: 10.1145/2095536.2095542
|View full text |Cite
|
Sign up to set email alerts
|

A workload-aware approach for optimizing the XML schema design trade-off

Abstract: In general, the design of XML schemas involves translating conceptual schemas into XML schemas which aim to be: (i) normalized schemas, and (ii) connected structures in order to achieve good performance on queries. However, these requirements address a trade-off because highly connected XML structures allow data redundancy, and normalized schemas generate disconnected XML structures. This paper describes a workload-based approach which balances this trade-off on translating conceptual schemas into XML structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This assumption is rooted on the so-called 20-80 rule, which says that 20 per cent of the operations produce 80 per cent of the application load. Our workload analysis identifies the concepts frequently accessed by transactions and is based on the workload modeling methodology defined in Batini et al (1992), Schroeder and Mello (2008) and Schroeder et al (2011). More details about the workload modeling methodology can be found in Lima and Mello (2015).…”
Section: The Conversion Processmentioning
confidence: 99%
“…This assumption is rooted on the so-called 20-80 rule, which says that 20 per cent of the operations produce 80 per cent of the application load. Our workload analysis identifies the concepts frequently accessed by transactions and is based on the workload modeling methodology defined in Batini et al (1992), Schroeder and Mello (2008) and Schroeder et al (2011). More details about the workload modeling methodology can be found in Lima and Mello (2015).…”
Section: The Conversion Processmentioning
confidence: 99%
“…if (min(e j ) ¼ ¼ 0 or (GAF(r i )<MAF or GUF(e j )>MUF)) then 16 establish a reference on tr(r i ) to each e k [ agg(r i ) Schroeder et al (2011), references generate extra costs in query processing because, in general, they execute value-based comparisons among several XML elements. However, we have observed that the costs for such comparisons can be reduced by defining text indexes on the referenced elements.…”
Section: Generating Xml Schemasmentioning
confidence: 99%
“…Translating conceptual schemas into XML schemas is not a straightforward process, given that conceptual schemas are complex graphs to be represented by XML trees. In a previous work (Schroeder et al, 2011), we have addressed a trade-off found in such translation process. Indeed, there are two opposite goals on generating XML schema, respectively:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations